Paraneoplastic Cerebellar Degeneration Associated with Gynecological Malignancy: Two Contrasting Case Reports - Salloum, George; Warwar, Ronald E.; Dyke, Jackie Van; Hemmings, David (Journal of Ocular Diseases and Therapeutics, 2014)
Paraneoplastic cerebellar degeneration is a rare neurologic disorder associated with several forms of cancer, including gynecological. It may present months or years prior to or after the diagnosis of cancer. Recognition of the condition is paramount for early diagnosis of the underlying malignancy and/or for mitigating the permanent effects of the cerebellar degeneration. We present two cases of paraneoplastic cerebellar degeneration associated with gynecological malignancies which illustrate the varied timings of presentation and outcomes of the disorder.